A regeneration-triggered metabolic adaptation is necessary for cell identity transitions and cell cycle re-entry to support blastema formation and bone regeneration - Brandão, Ana S. (2022)
Funding Funder Grant reference number Author Fundação para a Ciência e a Tecnologia PTDC/BIA-BID/29709/2017 Ana S Brandão Fundação para a Ciência e a Tecnologia PTDC/BTMSAL/29377/2017 Ana S Brandão Fundação para a Ciência e a Tecnologia UIDB/04462/2020 Ana S Brandão Fundação para a Ciência e a Tecnologia LA/P/0087/2020 Ana S Brandão Fundação para a Ciência e a Tecnologia LISBOA-01-0145- FEDER-022170 Ana S Brandão ATIP-Avenir Program Anabela Bensimon-Brito The funders had no role in study design, data collection and interpretation, or the decision to submit the work for publication.